Knowledge, Attitude, and Practices of Mothers Related to their Oral Health Status of 6-12 Years Old Children in Bhilai City, Chhattisgarh, India - Pawar, Pallavi; Kashyap, Nilotpol; Anand, Rohit (European Scientific Journal, ESJ, 2018)
Aim and Objectives: The aim of the study was to assess the oral health status of 6-12 year old children and their mother’s knowledge, attitude, and practices in Bhilai city. Moreover, this study was also carried out to determine whether mother’s oral health related knowledge, attitude, and practices have a significant influence on the oral health of their children. Materials and Methods: A cross- sectional study was conducted among children (n=600) aged between 6-12 years, attending both government and private schools accompanied with their mothers in Bhilai city. The oral health status of the children was evaluated by using WHO Oral Health Assessment Form (2013). The parents were then asked to fill 25 item based on selfadministered questionnaire. Mother’s knowledge, attitude, and practices were assessed by direct contact with mothers using close ended questionnaire. Statistical Analysis: The data was then entered and analysed using SPSS (Statistical Package for Social Sciences, SPSS Inc., Chicago, IL, USA). Also, p value≤ 0.05 was considered to be statistically significant. Results: The result of the study showed that 90% of mothers had good knowledge, 75% mothers had average attitude, and 51% mothers had high level practices related to oral health. An inverse relationship was found between children’s oral health status and their mother’s knowledge, attitude, and practices about oral health. Thus, the findings were highly significant. Conclusion: Results showed that mother’s oral health related to knowledge, attitude, and practices had a significant impact on oral health status of their children.